2009
DOI: 10.1590/s0100-06832009000500016
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of plant growth-promoting traits in clover-nodulating rhizobia strains isolated from different soils in Rio Grande do Sul state

Abstract: SUMMARYIn the last decades, the use of plant growth-promoting rhizobacteria has become an alternative to improve crop production. Rhizobium leguminosarum biovar trifolii is one of the most promising rhizobacteria and is even used with nonlegume plants. This study investigated in vitro the occurrence of plant growthpromoting characteristics in several indigenous R. leguminosarum biovar trifolii isolated from soils in the State of Rio Grande do Sul, Brazil. Isolates were obtained at 11 locations and evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
15
0
7
Order By: Relevance
“…The symbiotic rhizobia isolated from leguminous plants can promote plant growth not only through their biological N fixation ability (in leguminous plants) but also via their inherent PGP capacities: siderophores and indolic compound production and nutrient solubilization (Vargas et al 2009;Souza et al 2012;Ashraf et al 2013). This study indicated that the PGP ability most common among all isolates was indolic compounds production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symbiotic rhizobia isolated from leguminous plants can promote plant growth not only through their biological N fixation ability (in leguminous plants) but also via their inherent PGP capacities: siderophores and indolic compound production and nutrient solubilization (Vargas et al 2009;Souza et al 2012;Ashraf et al 2013). This study indicated that the PGP ability most common among all isolates was indolic compounds production.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobia species are considered legume endosymbionts as they can promote plant growth through biological nitrogen fixation, the production of hormones and enzymes, and the solubilization of soil nutrients (Schloter et al 1997;Vargas et al 2009). Strains belonging to several species of the rhizobia genera have previously been isolated from the root nodules of leguminous plants (Zhang et al 1991;Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, nas últimas décadas, outros micro-organismos têm atraído a atenção dos pesquisadores, com vista a uma potencial utilização na agricultura (VARGAS et al, 2009). As bactérias presentes na rizosfera são capazes de contribuir para o aumento da produtividade de algumas lavouras devido à colonização das raízes e estímulo ao crescimento das plantas.…”
Section: Introductionunclassified
“…Diversos micro-organismos vêm sendo relatados como promotores de crescimento em plantas, que incluem os gêneros Azoarcus, Azospirillum, Azotobacter, Arthrobacter, Bacillus, Clostridium, Enterobacter, Gluconacetobacter, Pseudomonas e Serratia, os quais são exclusivamente microorganismos não simbióticos (VARGAS et al, 2009). Além desses micro-organismos, estudos comprovaram a ação benéfica de rizóbios na atividade de promoção de crescimento vegetal em diversas espécies de plantas, a exemplo de milho, sorgo, milheto, canola, alface, mostarda, arroz, cevada (MATIRU & DAKORA, 2004;PERRINE-WALKER et al, 2007).…”
Section: Introductionunclassified
See 1 more Smart Citation